Pembuatan istem Informasi Nilai Akademik Berbasis SMS Gateway Pada SMP Negeri 3 Pringkuku Pacitan - Anjar Priyadna; Berliana Kusuma Riasti (Indonesian Journal of Networking and Security (IJNS), 2013)
Abstract - There are several problems of parents in knowing the development of their children in school. In this case the object takes place SMP N 3 Pringkuku. Usually parents get the value of student learning outcomes at the end of the semester. Maybe some of them do not know the development of their children during the school before obtaining score report at the end of semester. Perhaps it is because parents are too busy, or child who is less open to this parents, or parents who are far outside the city or province. To solve this problem done some build. Research methods used include : methods of interviews with school parties involved, methods of observation of the documents or data from school, and methods of literature to find the data needed from books, articles, or other literature related to the problem object. This system can be used to determine the value of information subjects the student via SMS. All messages can be monitored and addressed by the computer when the format of the message sent according to the procedure. The result of problem analysis found that parents only get reporting of student information at the end evary semester so they are difficult to monitor the development of student learning outcomes in schools. It is expected that the student's academic information system based on SMS Gateway can help the problems of the parents in knowing the development of the children in school and assist teachers in delivering value to the students' parents.   Abstrak - Ada beberapa masalah orang tua dalam mengetahui perkembangan anak-anak mereka di sekolah. Dalam hal ini penelitian dilakukan di SMP N 3 Pringkuku. Orangtua Biasanya mendapatkan nilai hasil belajar siswa pada akhir semester. Mungkin beberapa dari mereka tidak tahu perkembangan anak-anak mereka selama sekolah sebelum memperoleh laporan nilai di akhir semester. Mungkin karena orang tua terlalu sibuk, atau anak yang kurang terbuka ke orang tua, atau orang tua yang jauh di luar kota atau provinsi. Untuk mengatasi masalah ini dilakukan beberapa. Metode penelitian yang digunakan meliputi: metode wawancara dengan pihak sekolah yang terlibat, metode pengamatan terhadap dokumen atau data dari sekolah, dan metode studi pustaka untuk mencari data yang diperlukan dari buku, artikel, atau literatur lain yang berkaitan dengan objek masalah. Sistem ini dapat digunakan untuk mengetahui informasi nilai mata pelajaran siswa melalui SMS. Semua pesan dapat dimonitoring dan ditanggapi oleh computer apabila format pesan yang dikirim sesuai prosedur. Hasil analisis masalah menemukan bahwa orang tua hanya mendapatkan pelaporan informasi mahasiswa di semester akhir Seminggu sekali sehingga mereka sulit untuk memantau perkembangan hasil belajar siswa di sekolah. Diharapkan dengan adanya sistem informasi nilai akademik siswa berbasis SMS Gateway ini bisa membantu permasalahan orang tua siswa dalam mengetahui perkembangan nilai anaknya disekolah dan membantu guru dalam menyampaikan nilai hasil belajar siswa kepada orang tua siswa. Kata kunci:  Sistem,Informasi,Nilai,Siswa,sms